Light follower systems for visually impaired using visible light communication - Arsyad Ramadhan Darlis; Lucia Jambola; Tedi Hadyansyah (Universitas Ahmad Dahlan, 2021)
Visual impairment is the condition of someone who has a disorder or an obstacle in their vision. In this research, the implementation of light follower systems for visually impaired using visible light is proposed. This system can enable visually impaired people to determine orientation and support mobility, especially in an indoor situation, using visible light. The prototype of the visually impaired pathway was made as visible light communication (VLC) transmitter consisting of a 12 V power supply, light emitting diode (LED), MPEG-1 Layer-3 (MP3), and band pass filter (BPF) filter circuit. The VLC receiver is made a prototype of a blind stick consisting of a photodiode, amplifier, buzzer, timer, and 9 V battery. The measurement of this system uses acrylic and color filters with system accuracy taking into account the angle and conditions when the fluorescent lights are turned on and off. This result showed the system could transmit audio signals at a frequency of 3000 Hz. Furthermore, the comparison results showed that the quality of measurements without using a filter is better than using a filter. The output voltage value without using a filter with an angle of 700 degree is 7.19 Vp-p, meanwhile using a filter with an angle of 700 degree is 6.48 Vp-p.